Association between nut consumption and metabolic syndrome in Korean adults: results from the Korean Genome and Epidemiology Study–Health Examinees - Shin, Hye Ran; Song, SuJin (Frontiers in Nutrition, 2024)
The epidemiological evidence regarding nut consumption and metabolic diseases focuses on Western populations. Nut consumption among Koreans is relatively low, and the prevalence of metabolic syndrome is rapidly increasing, highlighting the need for more focused studies in this population. This cross-sectional study aimed to investigate the relationship between nut consumption and metabolic syndrome in Korean adults. A total of 112,501 adults (39,481 men and 73,020 women) aged 40–79 years were selected from baseline data of the Korean Genome and Epidemiology Study–Health Examinees. Nut consumption was assessed using a validated semi-quantitative food frequency questionnaire and categorized as non-consumers, <1 serving/week, ≥ 1 to < 2 servings/week, or ≥ 2 servings/week (15 g per serving). Metabolic syndrome and its components were defined according to the Korean Society of CardioMetabolic Syndrome criteria. Associations between nut consumption and metabolic syndrome and its components were examined using multiple logistic regression with adjustments for potential confounders. In the study population, the prevalence of metabolic syndrome was 21.4% (26.9% in men and 18.4% in women), and the mean nut intake was 0.8 serving/week (0.7 serving/week in men and 0.8 serving/week in women). After adjusting for confounders, higher nut consumption was associated with a lower odds ratio (OR) of metabolic syndrome in individuals consuming ≥ 2 servings/week compared with non-consumers (OR = 0.85, 95% confidence interval (CI) = 0.80–0.91, p for trend <0.001). Specifically, in men, this level of consumption was associated with a 14% reduction in the OR of metabolic syndrome (OR = 0.86, 95% CI = 0.77–0.95, p for trend = 0.028). In women, a similar reduction of 14% was observed (OR = 0.86, 95% CI = 0.80–0.93, p for trend <0.001). Among the metabolic syndrome components, nut consumption was inversely associated with abdominal obesity, low high-density lipoprotein-cholesterol, and elevated triglycerides in men and women, whereas no associations were observed for elevated blood pressure or elevated fasting blood glucose. Our findings suggest that higher nut consumption is inversely associated with metabolic syndrome and its components in Korean adults. Further studies are needed to examine the longitudinal association between nut consumption and metabolic diseases in this population